IL-6, TNF-α, IL-10, and nutritional status in pediatric patients with biliary atresia, - Maria Ines de Albuquerque Wilasco; Carolina Uribe-Cruz; Daniele Santetti; Gabriel Rodrigo Fries; Cristina Toscani Leal Dornelles; Themis Reverbel da Silveira
Abstract Objectives: The objective of the present study is to evaluate whether IL-6, TNF-α, IL-10 are associated with nutritional status in patients with cirrhosis secondary to biliary atresia and compare to healthy controls. Methods: The parameters used for nutritional assessment were the standard deviation scores of height-for-age and of triceps skinfold thickness-for-age. The severity of cirrhosis was evaluated using the Child-Pugh score and PELD/MELD. Serum cytokines were measured using Cytometric Bead Array flow cytometry. Results: IL-6, TNF-α, and IL-10 were significantly higher in the cirrhosis group when compared with the control group (2.4 vs. 0.24 (p < 0.001), 0.21 vs. 0.14 (p = 0.007), and 0.65 vs. 0.36 (p = 0.004), respectively. IL-6 and IL-10 were positively correlated with disease severity (0.450 [p = 0.001] and 0.410; [p = 0.002], respectively). TNF-α did not show a significant correlation with disease severity (0.100; p = 0.478). Regarding nutritional evaluation, IL-6 was negatively correlated with the standard deviation score of height-for-age (−0.493; p < 0.001) and of triceps skinfold thickness-for-age (−0.503; p < 0.001), respectively. IL-10 exhibited a negative correlation with the standard deviation score of height-for-age (−0.476; p < 0.001) and the standard deviation score of triceps skinfold thickness-for-age (−0.388; p = 0.004). TNF-α did not show any significance in both anthropometric parameters (−0.083 (p = 0.555) and −0.161 (p = 0.253). Conclusion: The authors suggest that, in patients with cirrhosis secondary to biliary atresia, IL-6 could be used as a possible supporting biomarker of deficient nutritional status and elevated IL-10 levels could be used as a possible early-stage supporting biomarker of deteriorating nutritional status.